Novel low-cost control system for large high-speed corn precision planters - Ding, Youqiang; Yang, Li; Zhang, Dongxing; Cui, Tao; Li, Yuhuan; Zhong, Xiangjun; Xie, Chunji; Ding, Zhengliang (International Journal of Agricultural and Biological Engineering, 2021)
Large high-speed corn precision planters can significantly improve seeding efficiency, but at present, there is no mature control technology in China. This study proposed a novel low-cost control system for large high-speed corn precision planters based on multiple technologies such as embedded systems, controller area network (CAN), global positioning system (GPS), and Android development technology. The developed control system provided excellent expansion capabilities of more than 40 planter rows. Functions such as monitoring the planter status, adjusting seed density, calculating planting-area were realized. Field experiments were performed under different GPS frequencies (fGPS), travel speeds, and seed spacings. Results showed that the working area relative error index (REI) and fGPS were negatively correlated, and the planter can achieve 0.84% error under the fGPS of 10 Hz. When the travel speed was 10 km/h or 12 km/h, the average quality index (QI), miss index (MI), and precision index (PI) were superior to 92.84%, 5.80%, and 18.57% under each seed spacing, respectively, QI and MI had no significant difference under each seed spacing (p<0.05). For a travel speed of 14 km/h, indexes values reached the worst level at seed spacing of 20 cm, but still met the requirements of Chinese national standards. The total cost of the control system for a 12-row corn precision planter is only 17.07% of similar products from abroad. In summary, the developed control system can achieve preferable performance and costs much less than similar products obtained from abroad, which is suitable for promotion in China or other developing countries. Keywords: corn precision planter, control system, Android, CAN bus, GPS DOI: 10.25165/j.ijabe.20211402.6053 Citation: Ding Y Q, Yang L, Zhang D X, Cui T, Li Y H, Zhong X J, et al. Novel low-cost control system for large high-speed corn precision planters. Int J Agric & Biol Eng, 2021; 14(2): 151–158.